Implementation of organization culture by functional Widyaiswara on human resources development agency of South Sulawesi Province - Hasyim, Hasriana (MEC-J (Management and Economics Journal), 2018)
The research problem in generally is how the application of organization culture by functional widyaiswara in implementation of organization goal on Human Resources Development Agency of South Sulawesi Province. The research approach in qualitative descriptive with type of research is phenomenon to illustrate in narrative or textual in observed of application the organizational culture on Human Resources Development Agency of South Sulawesi Province. The technique of data analysis through the gathered of information, reduction, display and preparation of information, take of conclusion or verification. The application of organizational culture by widyaiswara functional on Human Resources Development Agency of South Sulawesi Province showed that the organizational culture such as innovative, attention, result oriented teamwork, aggressive and stability in work to actualization of widyaiswara that increased the organization goal. Widyaiswara must have the ability that innovative in applied of task, appointment of high attention suitable with the competence, widyaiswara able to achieve of result oriented suitable with the goal, able to development of team work with doing of aggressive and achieve of stability in work. The six of organizational culture have the important role in achieved of organization goal.Â Keywords: Organizational Culture, Innovative, Attention, Result Oriented, Teamwork, Aggressive and Stability in Work